Strategies to terminate summer cover crops for weed management in no-tillage vegetable production in southeast Brazil - Branco, Roberto Botelho Ferraz; De Carvalho, Fernando; Oliveira, João Paulo; Da Costa Alves, Pedro Luis [UNESP] (Cambridge University Press (CUP), 2022)
Cover crop residue left on the soil surface as organic mulch in no-tillage crop production provides several environmental benefits, including weed suppression. Thus, many farmers who use cover crops attempt to reduce the use of agricultural inputs, especially herbicides. Therefore, our objectives were to study the potential of different cover crop species to suppress weeds and produce an in situ organic mulch and to evaluate the effect of the organic mulch with and without spraying glyphosate on weed suppression for vegetable (tomato [Solanum lycopersicum L.] and broccoli [Brassica oleracea L. var. botrytis]) growth and yield. Five cover crop treatments (sunn hemp [Crotalaria juncea L.], jack bean [Canavalia ensiformis (L.) DC.], pearl millet [Pennisetum glaucum (L.) R. Br.], forage sorghum [Sorghum bicolor (L.) Moench ssp. bicolor], and no cover crop [control]) were used in the main plots; and glyphosate was or was not sprayed on the flattened cover crop in the subplots of this split-plot experimental design. Organic mulch from pearl millet, sorghum, and sunn hemp resulted in lower weed biomass during the early seasons of both tomato and broccoli than mulch from jack bean and no cover crop (control). Spraying glyphosate after roller-crimping reduced weed biomass by 103 g m-2 and 20 g m-2 by 45 and 60 d after transplanting (DATr) of tomato, respectively, and resulted in a better tomato yield compared with not spraying. Glyphosate reduced weed biomass by 110 g m-2 in the early season of broccoli (30 DATr) but did not affect yield. Terminating high-biomass cover crops with a roller-crimper is a promising technique for weed management in vegetable crops that has the potential to reduce or even eliminate the need for herbicide.
Keywords: Brassica oleracea var. italica Plenck; Glyphosate; Organic mulching; Roller-crimper; Solanum lycopersicum L.; Weed suppression